480 Feeding a rumen-degradable amino acid impacts T3. (7th December 2018) - Hultquist, K; Kass, C; Clapper, J; Casper, D
Abstract: Our previous published work demonstrated that feeding rumen degradable valine to late-lactation dairy cows increased milk production compared to control fed cows with a response that was equivalent to recombinant bovine somatotropin. To further elucidate the response mechanism, our hypothesis was that thyroxine (T4) and triiodothyronine (T3), which are important for metabolism, may be involved. Previous short-term studies have demonstrated increased milk production when feeding iodinated casein. Eight multiparous Holstein dairy cows (255 ± 26.4 d in milk) were blocked by milk yield (34.1 ± 8.25 kg/d) and randomly assigned to 1 of 4 treatments using a replicated 4 × 4 Latin square design with 21-d periods (7 d for dietary adaptation and 14 d for data collection). Treatments were control (CON), a single injection of recombinant bovine somatotropin (rbST), and synthetic valine fed at 40 (V40) and 80 g/cow/d (V80). Cows were fed a total mixed ration with a distillers dried grains carrier fed at 113.4 g/d containing none or added amino acid. Blood samples were collected twice during wk 2 and 3 of each period for T3 and T4 analysis. Thyroxine concentrations (3.28, 3.90, 3.98, and 3.87 µg/dL for CON, rbST, V40, and V80, respectively) were increased (P < 0.05) for cows receiving rbST, V40, and V80 compared to CON cows. Triiodothyronine concentrations (125.7, 140.7, 148.8, and 139.7 ng/dL) were increased (P < 0.05) for cows receiving rbST, V40, and V80 compared to CON cows, with cows receiving V40 having the highest (P < 0.05) concentrations of T3. In conclusion, feeding rumen degradable valine increases blood T4 and T3 concentrations which could be the mechanism behind increased milk production.